2011
DOI: 10.1264/jsme2.me10193
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Cyanobacterium Synechococcus leopoliensis CCAP1405/1 on Agar Media in the Presence of Heterotrophic Bacteria

Abstract: The cyanobacterium Synechococcus leopoliensis CCAP1405/1 does not grow on common solid media made of agar, agarose HT, noble agar, gelrite and gelatin, although it grows in liquid media with the same components. The inoculation of S. leopoliensis CCAP1405/1 at a high initial cell density allowed it to grow on the agar media, and co-inoculation with one of the heterotrophic bacterial strains belonging to a wide range of phylogeny, showed the same effects even at a low initial cell density of S. leopoliensis CCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…This increase indicates that the eukaryotic heterotroph may provide additional benefits to phototrophic partners in addition to HOOH elimination in order to support the growth of cyanobacteria even more. Previous studies have shown that the addition of thiosulfate, vitamin B12, biotin, and thiamine can be used to enhance and elevate the growth of the cyanobacterium Synechococcus leopoliensis CCAP1405/1 [44]. …”
Section: Resultsmentioning
confidence: 99%
“…This increase indicates that the eukaryotic heterotroph may provide additional benefits to phototrophic partners in addition to HOOH elimination in order to support the growth of cyanobacteria even more. Previous studies have shown that the addition of thiosulfate, vitamin B12, biotin, and thiamine can be used to enhance and elevate the growth of the cyanobacterium Synechococcus leopoliensis CCAP1405/1 [44]. …”
Section: Resultsmentioning
confidence: 99%
“…WH2K promotes specific adherence of the epibionts to the cyanobacterial heterocysts (Stevenson and Waterbury, 2006; Behrens et al, 2008; Stevenson et al, 2011). Many cyanobacteria grow more efficiently in co-cultivation with heterotrophic bacteria than in axenic cultures, especially when heterotrophic remineralization of organic carbon alleviates cyanobacterial carbon limitation (Lupton and Marshall, 1981; Schiefer and Caldwell, 1982; Morris et al, 2008; Abed, 2010; Hayashi et al, 2011; Shen et al, 2011). Specific, highly-adapted interspecies interactions improve nutrient (Paerl, 1977; Paerl and Kellar, 1978; Lupton and Marshall, 1981; Li et al, 2010; Roe et al, 2012; Van Mooy et al, 2012) and vitamin (Gordon et al, 1969; Kazamia et al, 2012; Xie et al, 2013) acquisition by cyanobacteria and eukaryotic microalgae in consortia.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of behavioral responses varies greatly, as the origin of excreted material ranges from targeted secretion of photosynthetic intermediates (for example, glycolate, osmolytes and fatty acids) and extracellular polymeric substance (Seymour et al, 2010;Bruckner et al, 2011), to the products of cell lysis that can include sugars, proteins, lipids and nucleic acids (Grossart, 1999;Stevenson and Waterbury, 2006;Shen et al, 2011). In exchange, heterotrophic bacteria are thought to provide essential micronutrients, such as vitamins, amino acids and bioavailable trace metals (Amin et al, 2009;Hayashi et al, 2011;Kazamia et al, 2012;Xie et al, 2013), necessary to maintain high photosynthetic productivity.…”
Section: Introductionmentioning
confidence: 99%